Musculoskeletal disorders among teachers: a systematic review and meta-analysis - Tahernejad, Somayeh; Hejazi, Anahita; Rezaei, Ehsan; Makki, Faezeh; Sahebi, Ali; Zangiabadi, Zahra (Frontiers in Public Health, 2024)
As a result of the demands of their profession, teachers encounter a range of ergonomic risk factors and are highly susceptible to developing musculoskeletal disorders (MSDs). Accordingly, this systematic review and meta-analysis was carried out to examine the frequency of MSDs among teachers.The present research followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and its protocol was registered in international prospective register of systematic review (PROSPERO) under the code CRD42024509263. To conduct the searches, various databases such as PubMed, Scopus, Web of Science, Science Direct, SID, ISC, and Google Scholar were utilized, and the search period was until February 7 th, 2024 without time restriction. A random effects model was employed for meta-analysis, and I 2 index was utilized to assess heterogeneity among the studies. Data analysis was carried out using STATA (version 14).Results: After an initial search across the mentioned databases, a total of 2,047 articles were identified. Following screening, study selection, and quality evaluation, 44 studies were ultimately chosen for meta-analysis, involving 15,972 teachers. The results of the meta-analysis revealed that the overall prevalence of MSDs among teachers is 68% (95% CI: 61-75, I 2 = 99.2%, p < .001). Furthermore, the prevalence rates of MSDs in different body regions, such as the neck (47%), lower back (47%), shoulder (44%), upper back (37%), knee (35%), ankle (30%), wrist (27%), hip (22%), and elbow (13%), were reported.The overall prevalence of MSDs among teachers is relatively high. Neck and lower back pain are more common among them compared to other body regions. It is recommended that periodic Musculoskeletal disorders among teachers 2 occupational medicine examinations, training, and the implementation of ergonomic interventions for this occupational group focus on assessing the risk factors for MSDs, especially in the neck and lower back regions.